FRI0111 Anti-citrullinated protein antibody reactivities in treatment naÏve early rheumatoid arthritis. (15th June 2017) - Jonsson, MK; Hensvold, AH; Hansson, M; Mathsson-Alm, L; Aga, A-B; Sexton, J; Fevang, B-TS; Lillegraven, S; Catrina, AI; Haavardsholm, EA
Abstract : Background: An increase in the number of anti-citrullinated protein antibodies (ACPA) reactivities precede RA onset, and may be involved in the pathogenesis of the disease. The presence of ACPA is associated with radiographic progression in RA, and it has been suggested that ACPAs with different reactivities may be associated with different phenotypes of RA. Objectives: To assess the prevalence of baseline ACPA reactivities in an inception cohort of early RA patients, including subgroups based on anti-CCP/RF status, and to compare the findings to healthy controls. Methods: 217 DMARD-naïve early RA patients from the ARCTIC trial (1) were analysed. Radiographs were scored according to van der Heijde Sharp (vdHS) score. Anti-CCP status was analysed by FEIA (pos. if ≥10 IU/mL) and RF by ELISA (pos. if ≥25 IU/mL). ACPA titres (AU/ml) were considered pos. if above the 98-perc. of values in 619 non-RA subjects. Analysis of 13 ACPA reactivities targeting citrullinated peptides from fibrinogen, alpha-1 enolase, vimentin, fillagrin and histone was performed at baseline in patients and 94 controls (blood donors matched for age/gender/smoking), using a multiplex chip-based assay (2). Results: Baseline characteristics are presented in the table. The figure shows the prevalence of ACPA reactivities in the subgroups, with median [IQR] number of antibody reactivities in all patients 7 [3, 10], compared to 0 [0, 0] in controls (p<0.001). The corresponding numbers were 8 [5, 10] and 0 [0, 1] for the anti-CCP+ vs. anti-CCP- patients (p<0.001), and 8 [5, 10] and 2 [0, 7.5] for the RF+ vs. RF- patients (p<0.001). Positivity for ACPA reactivities was seen mainly in the anti-CCP+ and RF+ patients, but also occurred more frequently in RF- and anti-CCP- patients (table) than in controls (anti-CCP- vs controls p=0.037, RF- vs controls p<0.001). Conclusions: Prevalence of ACPA reactivities differed in subgroups of DMARD-naïve early RA patients according to anti-CCP and RF status. All RA subgroups, including RF- and anti-CCP- patients, had higher prevalence of ACPA reactivities compared to healthy controls. References: Haavardsholm et al BMJ 2016. Hansson et al Arthr Res Ther 2012. Disclosure of Interest: M. Jonsson: None declared, A. Hensvold: None declared, M. Hansson: None declared, L. Mathsson-Alm Employee of: Thermo Fisher Scientific, A.-B. Aga: None declared, J. Sexton: None declared, B.-T. Fevang Grant/research support from: Novartis, S. Lillegraven: None declared, A. Catrina: None declared, E. Haavardsholm Grant/research support from: AbbVie, MSD, Pfizer, Roche, UCB